Job insecurity and wage outcomes in Britain - David Campbell; Alan Carruth; Andrew Dickerson; Francis Green (University of Kent, Department of Economics, 2001)
In 1996 and 1997, approximately 1 in 10 British workers thought that it was either likely or very likely that they would lose their job within 12 months. Increased job insecurity has been touted as a possible cause for the decline of equilibrium unemployment in Britain and the United States during the 1990s. We investigate whether perceptions of job insecurity contribute to lowering wages. First, we examine the validity of subjective questions about unemployment expectations, using longitudinal data. We find that workers' fears of unemployment are increased by their previous unemployment experience and by other household members' unemployment experiences, and are associated with other objective indicators of insecure jobs. The measure of unemployment fear also helps to predict future unemployment, above and beyond conventional objective variables. We then show that high fear of unemployment is associated with significantly lower wage levels. OLS estimates of the downward impact on average wages of an increase in this expectation by just one half of a standard deviation are approximately 1 percent. Instrumental variable estimates suggest that 1 percent is likely to be an underestimate. We conclude that increased job insecurity, relative to aggregate unemployment, has contributed in part to wage restraint in Britain.
Keywords: J28; C21; C23; J31; 330; unemployment expectations; job satisfaction; cross-section models; panel data; wage level and structure; Arbeitsplatz; Arbeitslosigkeit; Lohnstruktur; Großbritannien; Personalabbau